DEVELOPING A FUN POP-UP BOOK TO TEACH ENGLISH IN THE KINDERGARTEN - Aisyah Ayyu Nuurhabibah; Siti Rofi'ah; Tyas Alhim Mubarok (PROJECT (Professional Journal of English Education), 2023)
In the era of globalization, English is one of the subjects that students must comprehend to follow and adapt to society. However, in Indonesia the English introduction and fundamental education that pupils receive in elementary and kindergarten are still poor. This research leads to the developing of a Fun Pop-Up book for kindergarten pupils at RA Perwanida Sumberjati. The researchers analyzed the requirements of kindergarten students by observing and interviewing them to determine their study habits. The results assisted the researchers in determining the types of media that could attract pupils'' attention. In this research, the researchers develop a book in the form fun pop-up book to improve kindergarten pupils'' English mastery. Therefore, the researchers use Research and Development (R&D) as a research design. The development procedure used in the research is the ten steps Borg & Gall development model. The result of the media validation score obtained a value of 97.5% for the Very "Valid category" and "Very Valid" categories, with a validation value of 92.5% obtained from material validation. This percentage indicates that this Fun Pop-Up Book for Teaching English in Kindergarten is effective.